ANALYSIS OF PRESCRIPTION PATTERNS AND ADVERSE DRUG REACTIONS IN REPRODUCTIVE-AGE WOMEN (15–44 YEARS) WITH URINARY TRACT INFECTIONS: A RETROSPECTIVE STUDY FROM CENTRAL INDIA - GAYATRI RAVINDRA PATIL; SUSHIL KUMAR VARMA (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Analysis of drug prescription patterns used in the treatment of urinary tract infection among the reproductive age groups, which is between 15 and 44 years. Analysis of adverse effects of drugs prescribed in urinary tract infection (UTI) among reproductive age groups of patients aged between 15 and 44 years to be studied. Methods: This retrospective study analyzed records of 47 female UTI patients (15–44 years) over 18 months in a rural Central Indian hospital. It assessed prescription patterns, data completeness, antibiotic trends, and ADRs. Descriptive frequency and percentage was performed; no inferential statistics were conducted. Results: Nitrofurantoin (63.83%) was the most commonly prescribed antibiotic for UTIs, followed by fluoroquinolones (14.9%) and fosfomycin (10.64%). Supportive therapies, such as Lactobacillus and sodium bicarbonate, were frequently co-prescribed. Significant prescription faults were detected with high frequency in dosage form (95.74–100%), amount, and duration. In 44% of patients, ADRs were found to occur, out of which the most frequent were diarrhea (40%). Medications such as amoxicillin-clavulanic acid and phenazopyridine presented with particular ADRs. Conclusion: Nitrofurantoin must continue to be a first-line treatment for UTIs in the face of prescribing mistakes and high ADRs because improved monitoring of patient outcomes reinforces prescribing habits and will help counteract antimicrobial resistance.